Use of fatigue assessment scale and small fiber neuropathy screening list in Japanese patients with sarcoidosis - Tomioka, Hiromi; Kobayashi, Yu; Iwabayashi, Masaaki; Lee, Masamichi; Matsuoka, Tasuku; Yokota, Makoto; Amimoto, Hisanori; Takiguchi, Junji; Kaneko, Masahiro; Fujii, Hiroshi (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2025)
Background: The Fatigue Assessment Scale (FAS) and Small Fiber Neuropathy Screening List (SFNSL) are widely used in Western countries to investigate symptoms associated with fatigue and small fiber neuropathy (SFN). However, few studies have used these patient-reported outcome measures (PROMs) in Japan. Methods: This was a cross-sectional and longitudinal study at an outpatient clinic in a community teaching hospital in Japan. Participants completed the FAS, SFNSL, and Short Form-36. Clinical parameters, including angiotensin-converting enzyme (ACE) and soluble interleukin-2 receptor (sIL2R), were derived from the medical records of the patients. Results: The study population included 55 patients (29 males; 26 females; mean age: 59±15 years; median disease duration: 5.0 years). Eleven patients received a systemic corticosteroid. The mean FAS score was 22.7±8.2; 27 patients (49.1%) and five patients (9.1%) indicated fatigue (score: ≥22) and extreme fatigue (score: ≥35), respectively. The mean SFNSL score was 13.8±14.3; 23 patients (41.8%) and two patients (3.6%) indicated probable/highly probable SFN (score: 11–48) and SFN (score: ≥49), respectively. The FAS score exhibited strong correlations with physical function, vitality, and mental health of Short Form-36. The SFNSL score exhibited strong correlations with bodily pain and vitality. Of the 55 patients, 45 completed the 1-year follow-up. There were no significant changes noted in the FAS score (mean: 0.04, 95% confidence interval: −1.29–1.38) and SFNSL score (mean: 0.31, 95% confidence interval: −2.12–2.74) during the follow-up. Within-subject changes in FAS and SFNSL scores showed moderate correlations with those of physical function and general health, respectively. There was no significant relationship between FAS or SFNSL score and ACE or sIL2R values at baseline and within-subject changes in these parameters during the follow-up. Conclusions: Approximately half of the patients suffered from fatigue or SFN. These nonspecific symptoms have a great effect on quality of life.